Advokatas Tadas Vrublevskis – lietuvių politinių bylų dalyvis - (:unkn) unknown (My University, 2011)
The aim of this small-scope study is to unveil the details of how Tadeusz Wroblewski handled Lithuanian’s political cases. The article analyses primary sources held by the Manuscript Department of the Wroblewski Library of the Academy of Sciences – those 54 files (out of approximately 470 kept in the personal Wroblewski’s collection (No 155)), which could be related to the lawyer’s participation in Lithuanians’ political court cases. Based on archival sources and available historiographical research, the article presents and evaluates Wroblewski’s activities in the cases related to Lithuanian national resurgence.
Lawyer Tadeusz Wróblewski as a participant on Lithuanians’ political cases
Skyriaus antraštė: Straipsniai